Comparative karyomorphology in populations of giant toad (Bufo marinus Linn.) in the Philippines - Doyungan, Zaldy F.; Barrion, Adelina A. (Asia life sciences :the international journal of life sciences., 1995)
"Three populations of giant toad Bufo marinus Linn. in the Philippines were surveyed for chromosomal variation. Karyotype analysis revealed that the toad has a diploid (2n) chromosome complement of 22. The mean relative lengths and centromeric indices of the 11 chromosome pairs in three populations did not vary significantly following Analysis of Variance. Chromosomes 5 and 6 differed significantly in the arm ration in all populations. Except for chromosome 4 which has a submedian centromere, all other chromosomes have median centromeres. Based on the relative lengths, the chromosomes were grouped into three categories: Group A (5 large chromosomes), Group B (4-5 intermediate chromosomes) and Group C (1-2 small chromosomes). No structural or numerical chromosomal abnormality was observed. The secondary constriction which is indicated by the achromatic region in the short arm of chromosome 7 was not always distinct and visible. C-banding was not observed in all chromosomes after several trials and modifications of Giemsa straining following Ba(OH)2 denaturation. Silver nitrate staining yielded invariant silver blocks in the nucleolus organizing region (AgNOR) in the short arm of chromosome 7."